Psychosocial Consequences of Infertility among Rural and Urban Population in Vijayapura, Karnataka - Patil, Vidya V; Udgiri, Rekha (National Journal of Community Medicine, 2019)
Background: The experience of infertility is clearly different from individual to individual, varying by gender, personality, culture, personal and family history as well as the investment they project in their forward-looking child. The study was conducted to assess the psychosocial consequences of infertility among rural and ur- ban residents. Methods: A cross sectional study was conducted in the rural and urban field practice area between March 2015- February 2016. Complete enumeration of all the houses was done to list all eligible couples and those who were exposed to pregnancy and had infer- tility were identified. A validated “Fertility problem inventory scale” was used to assess the psychosocial consequences of infertil- ity and impact was seen at four levels i.e., personal, sexual, social and marital. Results: Conflict within the marriage was highest (mean scores 61.5), followed by decline in sexual relationship (mean scores 51.4), social impact (mean scores 41.3) and personal impact(mean scores 38). Mean score difference was significant among primary and secondary infertility participants, men and women. Conclusion: The results revealed that the couples have poor well- being on all the dimensions. There is need of awareness generation and counselling.